PENGARUH ROE dan EPS TERHADAP HARGA SAHAM PERUSAHAAN PT LION METAL WORK Tbk - Sri Puspitadewi, Sinta; Fitria, Ade (Nusa Putra University, 2021)
The capital market is an activity related to securities trading and offerings that are universal. The capital market not only provides investors with other options, but also provides investors with various options, such as saving in a bank, buying gold, insurance, land and buildings, etc. The capital market is a link between investors and industry and government agencies by trading long-term instruments (such as bonds, stocks, etc.). The growth of the Indonesian capital market encourages companies to openly sell various shares to the public. Many companies have gone public. Investors are advised to be extra careful before making any investment decisions. Therefore, investors must first analyze the accounting information contained in the company. The number of shares sold to the public can be used as a good indicator of the company's effectiveness. Stock prices are directly affected by the information available in the financial statements, and there is an analysis of financial ratios that have a considerable influence on changes in stock prices. Therefore, the author chose to examine ROE and EPS on changes in the stock price of PT LION Metal Work which was listed on the Indonesia Stock Exchange from the period 2018 - 2020. The author's hypothesis above was tested using a multiple correlation test where the independent variables are ROE and EPS while the dependent variable is stock price. Based on research conducted using the F test and T test with a significance level of 0.05, it turns out that ROE and EPS have no significant positive effect on stock prices.